Digital Readiness Of Msmes In The Industry 4.0 Era: A Study On Culinary Sector Msmes In Tuntang Sub-District, Semarang Regency - Hardian, Hardian; Mohammad Halilintar (Jurnal Multidisiplin Indonesia, 2025)
This study examines the digital readiness of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Tuntang District, Semarang Regency in facing the Industry 4.0 era. The research employed a descriptive quantitative approach, involving 75 culinary MSME owners through questionnaires and structured interviews. The results show that the majority of culinary MSMEs in Tuntang District are at the "transition" level of digital readiness (62%), while 23% are still at the "basic" stage and only 15% have reached the "advanced" level. Factors influencing digital readiness include the digital literacy of business owners, availability of technological infrastructure, financial support, and demographic characteristics of business actors. The main challenges faced by MSME owners include limited knowledge of digital technology, minimal access to training, limited capital for technology investment, and the age of business actors who are predominantly over 40 years old. This research recommends the need for sustainable technical assistance programs, provision of special funding access for technology adoption, and development of a digital ecosystem that supports the transformation of local culinary MSMEs.